Investigation of the Unsteady Flow Behaviour on a Wind Turbine Using a BEM and a RANSE Method - Alesbe, Israa; Abdel-Maksoud, Moustafa; Aljabair, Sattar (Journal of Renewable Energy, 2016)
Analyses of the unsteady flow behaviour of a 5 MW horizontal-axis wind turbine (HAWT) rotor (Case I) and a rotor with tower (Case II) are carried out using a panel method and a RANSE method. The panel method calculations are obtained by applying the in-house boundary element method (BEM) panMARE code, which is based on the potential flow theory. The BEM is a three-dimensional first-order panel method which can be used for investigating various steady and unsteady flow problems. Viscous flow simulations are carried out by using the RANSE solver ANSYS CFX 14.5. The results of Case I allow for the calculation of the global integral values of the torque and the thrust and include detailed information on the local flow field, such as the pressure distribution on the blade sections and the streamlines. The calculated pressure distribution by the BEM is compared with the corresponding values obtained by the RANSE solver. The tower geometry is considered in the simulation in Case II, so the unsteady forces due to the interaction between the tower and the rotor blades can be calculated. The application of viscous and inviscid flow methods to predict the forces on the HAWT allows for the evaluation of the viscous effects on the calculated HAWT flows.